Supreme Student Government (SSG) and Class Officers: The Role of Emotions in Decision-Making and Leadership in Dr. Carlos S. Lanting College (Synergy: Cross-Disciplinary Journal of Digital Investigation (2995-4827), 2023)
Emotions are an essential component of human behavior, shaping personalities and character while also playing an important role in leadership and decision-making. This study investigates whether or not emotions indeed have an important role in the decision-making and leadership of student leaders at Dr. Carlos S. Lanting College. This study covers understanding the perception of emotions, identifying decision-making strategies, analyzing the impact of emotions on leadership effectiveness, and providing recommendations for leadership development. By fulfilling these objectives, the study will contribute to understanding how emotions influence student leaders' decision-making processes and provide practical recommendations for enhancing their leadership skills. The study used a phenomenological design to explore the role of emotions in leadership and decision-making among the Supreme Student Government and Class Officers. Purposive sampling is used to select 20 participants. Researchers gathered data through interview forms and analyzed it using thematic analysis to identify themes and patterns related to the role of emotions in leadership and decision-making. The results show that emotions indeed have an influence on leadership and decision-making. It has been seen through the data gathered that there are positive effects (confidence and creativity) and negative effects (impulsivity and irrationality). Secondly, it shows that motivation, positivity, optimism, positive thinking, resilience, and a good mindset as keys to being effective in leadership and decision-making. If they are feeling negative emotions or any emotions in general that might hinder their decision-making, they utilize strategies including self-awareness, open communication, calming techniques, and considering responsibilities and consequences. Lastly, the results underscore the importance of emotions in different aspects of leadership, such as building connections, influencing decision-making, and shaping team dynamics. All in all, emotions significantly impact the student leaders' decision-making and leadership. Recommendations include promoting positive thinking, open communication, and self-awareness. Apply these findings to enhance decision-making and leadership skills.